Mitochondrial DNA analysis: polymorphisms and pathogenicity. Issue 7 (1st July 1999) - Chinnery, Patrick F; Howell, Neil; Andrews, Richard M; Turnbull, Douglass M
Abstract : The investigation of mtDNA disease can be relatively straightforward if a person has a recognisable phenotype and if it is possible to identify a known pathogenic mtDNA mutation. The difficulties arise when no known mtDNA defect can be found, or when the clinical abnormalities are complex and not easily matched to those of the more common mitochondrial disorders. We will describe here the difficulties that can be encountered during the identification of pathogenic mtDNA mutations and the approaches that can be used to confirm, or eliminate, a likely pathogenic role, in either single gene diseases or in multifactorial disorders.